Penyerapan Ion Logam Merkuri Hg(II) oleh Biosorben dari Daun Lidah Mertua (Sansivieria sp.) - Elvitriana Elvitriana; Kasturi Kasturi; H Murni; Suhendrayatna Suhendrayatna (Jurnal Serambi Engineering, 2022)
The aim of this study was to apply a biosorbent from the leaves of Lidah Mertua (Sansivieria sp.) which were activated by 4M HCl to remove mercury metal ions Hg(II). The leaves of Sansivieria sp. were cleaned, dried in an oven, and carbonized in a furnace at a temperature of 450 oC for 1.5 hours. After grinding to a size of 50 mesh, the resulting carbon was activated using 4 M HCl for 24 hours and dried at 110 oC for 2 hours. The absorption ability test of biosorbents was carried out by mixing 2, 3, and 4 grams activated biosorbent in 200 ml of water containing 0.15 mg-Hg/L metal ions Hg(II). The mixture was stirred using an incubator shaker with variated contact times of 0, 4, and 6 days. Mercury metal ions concentration were analyzed using AAS, Shimadzu AA-6300. The results showed that activation using 4 M HCl can open the pores of the biosorbent. Compared to the inactivated biosorbent, the characteristics of this activated biosorbent were better with lower water content (2%), higher ash content (9.9%), greater iodine absorption (1259.14 mg/g), and higher carbon content (89%). Based on SNI.06-3730-1995 Standard, the resulting biosorbent was close to qualified as activated carbon. The highest absorption efficiency of ion Hg(II) was 99.6% which was achieved for 6 days with a 4 grams of biosorbent. The results of this study concluded that the leaves of (Sansivieria sp.) activated by 4M HCl could absorb metal ions Hg(II) well.